Identification Of Motor Skill Levels Of 10 - 12 Year Old Disability Students - Rendra, Rendra; Nurhasan, Nurhasan; Suroto, Suroto; Wahyu Hidayat, Zakaria (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
In this study aims to identify and find information related to the level of motor skills of 10-12 year old deaf students, the method in this study uses quantitative descriptive research methods, by describing current conditions without testing hypotheses. With the focus of research on the motor skills of children with disabilities aged 10-12 years. Retrieval using tests related to motor skills. The number of students who became subjects with a total of 20 students. Data analysis techniques in this study using descriptive data calculations and also percentage calculations. The results of descriptive calculations of research data obtained a maximum score of 13, minimun 3, an average of 8.75, and a standard deviation of 2.80. while for the percentage results it is known that the excellent category is 0 (0%), good 5 (25%), moderate 11 (55%), less 3 (15), and very less 1 (5%), the conclusion in this study based on the percentage is in the moderate category.